The morphology and ecology of the reefs of Sabah (West Coast) and Sarawak - Mohamed, Mohd. Ibrahim; Badaruddin, Zaharuddin (1991)
Studies revealed that the reefs of the islands off Sarawak's First Division are comparable if not better than the other much studied reefs of Malaysia in terms of species diversity, composition and distribution. The status of the reefs here can be classified as 'undisturbed'. A north - south orientation of coral reef formation on these islands is peculiar only to these region. Seaweed population is very high in between reefs. Coral fish studies indicate a wide variaty of species and are fairly homogeneous at all sites censured. All reefs are of the fringing types. The reefs of some Sabah west coast islands are mostly of the hallow fringing type. Some small patch reefs were observed to be closely associated with these shallow fringing reefs. Human activities i.e, explosive fishing, establishment residential areas, heavy water traffic etc., have caused considerable damage to some reefs. Fish studies indicate the presence of target and indicator species of coral fish at all sites surveyed.